GROUNDED THEORY DATA ANALYSIS - F Rafii; F Oskouie; Yadavar Nikravesh (Iran University of Medical Sciences, 2003)
Grounded Theory is a qualitative research approach used to explore the social processes that present within human interactions. Glaser and Strauss (1967) developed the method and published the first text addressing method issues. Grounded theory includes systematic techniques and procedures of analysis that enable the researcher to develope a substantive theory. The discovery of a core variable is the goal of grounded theory. The core variable serves as the foundational concept for theory generation. During the conduction of a grounded theory study, the processes of data collection, coding and analysis occur simultaneously. The three levels of open, axial, and selective coding constitutes the coding procedures. Memoing preserves emerging hypotheses, analytical schemes, hunches and abstractions. Saturation occurs after many rounds of coding, until no new categories emerge from the process. At this point, the researcher can begin determining the relationships between categories. A good report of research reflects the theory in such a way that allows an outsider to grasp its' meaning and apply its concepts. By doing grounded theory researcher makes a contribution to the body of knowledge.